Auditing Internal Quality Control Practices in a Large Size Clinical Biochemistry Laboratory - Jayesh Warade (Indian Journal of Medical Biochemistry)
Background: Auditing quality control practices is crucial for ensuring adherence to and compliance with the standard operating procedures of quality assurance. This study examines the internal quality control (IQC) practices in clinical biochemistry laboratories, focusing on their effectiveness in ensuring accurate and reliable test results. Materials and methods: A comprehensive audit was conducted every month, and records were reviewed periodically in a high-volume clinical biochemistry lab, assessing compliance with established IQC protocols and identifying areas for improvement. Chi-square test was used to assess any significant deviations in the practices from the established protocols. Results: Overall compliance with IQC practices was 98.8%. The compliance rates of 100% were observed for LJ Chart, Monthly CV%, measurement uncertainty, mean SD calculation, IQC lot verification, accuracy testing records, and kit verification records. Lower compliance rates were noted for patient moving average records at 95.8%. Out-of-control events occurred in 0.12% of the IQC tests. The overall average audit score for six months stands at 94.3%. Conclusion: The findings reveal very minimal variations in IQC implementation as compared to standard operating procedures and provide recommendations for enhancing quality control processes.